Design and Performance Analysis of a Biodiesel Engine Driven Refrigeration System for Vaccine Storage - Kamsuk, K; Damrongsak, D; Tippayawong, N (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
A compact, stand-alone, refrigeration module powered by a small biodiesel engine for vaccine storage in rural use was proposed. The engine was of single cylinder, four-stroke, direct injection with displacement of 0.296 cm3 and compression ratio of 20:1. The refrigeration system was modified from an automotive vapor compression system. The system performance was analytically investigated. From the simulation, it was found to have acceptable operation over a range of speeds and loads. Performance of the system in terms of fuel consumption and torque tended to decrease with an increase in engine speed. The modular system was able to operate at cooling loads above 4.6 kW, with proper speed ratio between the engine and the compressor. Overall, primary energy ratio of the refrigeration was found to be maximum at 0.54.